Proximate and ultimate explanations for flaunting exercise on social media: Associations between mate value, mate access, self-esteem, narcissism, and posting exercise-related content on social media - Lyytikäinen, Lotta (My University, 2025)
Flaunting exercise on social media is a widespread phenomenon, but scientific research is insubstantial. To the best of my knowledge, behavior or motives on social media have not been studied with taking both, evolutionary (i.e., mate value and mate access) and traditional (i.e., self-esteem and narcissism), psychology constructs into account. This thesis investigates associations between posting exercise-related content on social media and mate value, mate access, self-esteem, and narcissism. This thesis also explores the associations between mate-value-based motives (e.g. wishing that posting certain content would increase their own mate value) of exercise-related social media posting and mate value, mate access, self-esteem, and narcissism. The survey consisted of demographic information items, a brief self-esteem measure, a brief narcissism personality trait inventory, the Mate Value and the Mate Access Scales, and questions about posting exercise-related content on social media. Participants were approached through Finland’s higher education mailing lists and data collection continued from January to February in 2025. A total of 130 participants answered the survey, and they were all included in the study. High mate value, high levels of narcissism, and low self-esteem were expected to associate with high amounts of posting exercise-related content on social media. However, results did not support these hypotheses even though the model did have a statistically significant overall fit. The analysis with mate-value-based motives as a dependent variable also had a statistically significant overall fit of the model with small explanatory power. In this model, mate value and narcissism were associated with mate-value-based motives, and they had statistically significant independent explanatory power. Based on this study, it seems that mate value and narcissism may explain the mate-value-based motives of exercise-related posting. The relatively small sample size may have limited statistical power. Some participants reported that understanding questions about mate value was difficult, which may have also affected results regarding mate value. Further research could focus on developing reliable ways to measure posting behavior on social media independently from social media use.
Keywords: exercise, health, mating, narcissism, regression analysis, self-concept, social media